Association between helicobacter pylori infection and hyperemesis gravidarum - Elmahdy, M.; Elmarsafawy, A.; Elkafash, D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hyperemesis gravidarum is one of the serious problem affecting pregnant females. The main etiology is still unknown. Different theories were assumed. The objective of this study was to study the relationship between Helicobacter pylori infection and hyperemesis gravidarum. Methods: case control study of 80 cases (40 case of HEG) and (40 case of normal pregnant females. assessment of helicobacter pylori antibodies in serum and stool were done for both groups. Results: Helicobacter pylori in stool samples were positive in 75% of cases of HEG and positive in 37.50% of normal pregnant females. These results were statistically significant (p = 0.001). The prevalence of Hp IgG AB and HpSAB was 77.5% in the patients with HEG, and 55.0% in controls (P = 0.05). Conclusions: helicobacter pylori infection may be one of the risk factors for HEG. The prevalence of helicobacter pylori AB in both serum and stool is more in HEG cases than in normal pregnant females.